Mesosphere and Lower Thermosphere Winds and Tidal Variations During the 2019 Antarctic Sudden Stratospheric Warming. Issue 3 (12th March 2022) - Liu, Guiping; Janches, Diego; Ma, Jun; Lieberman, Ruth S.; Stober, Gunter; Moffat‐Griffin, Tracy; Mitchell, Nicholas J.; Kim, Jeong‐Han; Lee, Changsup; Murphy, Damian J.
Abstract: Realistic modeling of the winds and dynamical variations in the mesosphere and lower thermosphere (MLT) at Southern Hemisphere (SH) mid‐to‐high latitudes near 60°S where dramatic motions occur has been a challenge. This work presents an evaluation of the MLT zonal and meridional winds from ∼80 to 98 km altitude produced by the high‐altitude version of the Navy Global Environmental Model (NAVGEM‐HA) numerical weather prediction system during the Antarctic Sudden Stratospheric Warming (SSW) in September 2019. These results are compared with the coincident measurements by five meteor radars at Tierra del Fuego (TDF; 53.7°S, 67.7°W), King Edward Point (KEP; 54.3°S, 36.5°W), King Sejong Station (KSS; 62.2°S, 58.8°W), Rothera (ROT; 67.5°S, 68.0°W), and Davis (DAV; 68.6°S, 78.0°E) across SH mid‐to‐high latitudes. We find that the day‐to‐day variations in NAVGEM‐HA winds related to tidal motions are overall consistent with variations in the radar winds, and the daily mean winds have a correlation of 0.7–0.9 between them. Three‐hourly NAVGEM‐HA winds have a correlation of ∼0.5 and mean difference <10 m/s to the radar observations at most stations, and the Root Mean Square (RMS) error ranges from ∼25 to 35 m/s. Above 90 km altitude, the correlation coefficient decreases, and the difference and RMS error increase, indicating an upper limit to the validity of the NAVGEM‐HA results. Both the analyzed and observed winds reveal an enhancement in diurnal and semidiurnal tidal amplitude during this SH SSW. NAVGEM‐HA shows some evidence that nonmigrating tidal enhancements are produced through the interaction of migrating tides with planetary waves. Plain Language Summary: High Altitude (HA) meteorological analysis products of the Navy Global Environmental Model (NAVGEM) that assimilates various observations are believed to be able to provide a realistic description of the state of the mesosphere and lower thermosphere (MLT). Dramatic motions of the MLT region are detected during austral winter in the Southern Hemisphere (SH) over the area extending from the Southern Andes to the Drake Passage and the Antarctic Peninsula. Yet, due to lack of global wind observations, this dynamically active region has not been well explored. Sudden Stratospheric Warmings (SSWs) are manifestations of dynamic disruptions in the winter polar area, and in September 2019 an unusual SSW occurred over Antarctica. This study evaluates the evolution of MLT winds and related tidal variations during this SSW, using both the NAVGEM‐HA analysis results and the meteor radar observations at several locations within this very dynamic region. We have performed a one‐to‐one comparison and found that the analyzed daily mean winds generally agree with the observations. The NAVGEM‐HA numerical forecast system also captures the enhanced tidal motions observed by the radars during this Antarctic SSW. Key Points: High‐altitude meteorological analysis results with data assimilation are consistent with the meteor radar measurements near 60°S latitude Day‐to‐day variations in the zonal and meridional winds at ∼80–90 km altitude are captured by the analysis system Both analyzed and observed winds reveal a large tidal variation at ∼90 km altitude during the 2019 Antarctic stratospheric warming